Preterm Infant with Congenital Tracheal Diverticulum in the Presence of Esophageal Atresia and Tracheoesophageal Fistula - Alessandra Glover Williams; Janet McNally; Julian Gaskin; Ela Chakkarapani (EL-Med-Pub, 2018)
A 32+4-week-preterm neonate was operated on day 1 for esophageal atresia with tracheoesophageal fistula with a tight primary anastomosis and closure of a tracheoesophageal fistula. Postoperatively, he needed ventilation for 6 days. Post-extubation, he needed continuous positive airway pressure support for increased work of breathing, increasing oxygen requirement, and respiratory acidosis when respiratory support was weaned. Further, during the post-operative period, he had right hemidiaphragmatic paresis and acute lifethreatening events requiring manual high-pressure, non-invasive positive pressure ventilation resuscitation. These complications were considered, and a computed tomography assisted by three-dimensional reconstruction was performed. This revealed a congenital tracheal diverticulum and severe tracheomalacia which was confirmed with microlaryngoscopy and bronchoscopy. The presentation and the diagnostic dilemma surrounding this rare diagnosis are discussed in this case report.